2013
DOI: 10.1128/iai.00408-13
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility of IgA-Deficient Mice to Pulmonary Francisella tularensis Live Vaccine Strain Infection

Abstract: Francisella tularensis, the causative agent of tularemia, is most deadly in the pneumonic form; therefore, mucosal immunity is an important first line of defense against this pathogen. We have now evaluated the lethality of primary F. tularensis live vaccine strain (LVS) pulmonary infection in mice that are defective in IgA (IgA ؊/؊ mice), the predominant mucosal Ig isotype. The results showed that IgA ؊/؊ mice were more susceptible than IgA ؉/؉ mice to intranasal F. tularensis LVS infection, despite developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 29 publications
3
19
2
Order By: Relevance
“…Administration of IL-12 enhanced production of IFN-␥ by NK (12,28,29). Our data also demonstrated the critical role of IFN-␥ in IL-12-mediated protection against pulmonary MRSA.…”
Section: Discussionsupporting
confidence: 62%
“…Administration of IL-12 enhanced production of IFN-␥ by NK (12,28,29). Our data also demonstrated the critical role of IFN-␥ in IL-12-mediated protection against pulmonary MRSA.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, serum antibodies have been seen to be capable of conferring protection against lethal respiratory LVS challenge when administered therapeutically up to 48 h post-exposure [15]. This role of antibodies has been documented further by data from IgAdeficient mice that were highly susceptible to primary pulmonary LVS infection [16] and were unable to survive lethal challenge after vaccination [17]. The experiments with IgA À/-mice, moreover, provide examples of the cross-talk among the B cells (and/or their products) and other immunocompetent cells.…”
Section: Introductionmentioning
confidence: 87%
“…The experiments with IgA À/-mice, moreover, provide examples of the cross-talk among the B cells (and/or their products) and other immunocompetent cells. Moreover, IgA À/-mice were observed to have in particular decreased numbers of IFN-g-secreting CD4 þ and CD8 þ T cells in the lung on day 9 postinfection, lower pulmonary IFN-g levels, and, at early time points, reduced levels of IL-12 [16].…”
Section: Introductionmentioning
confidence: 96%
“…After the cells were treated with haemolytic buffer (0Á144 M NH 4 Cl/ 0Á017 M Tris-HCl, pH 7Á65), the remaining cells were incubated with a cocktail of biotinylated anti-CD3, biotinylated anti-B220, biotinylated anti-CD11b and biotinylated antiCD11c mAbs (all from BD Biosciences), followed by incubation with streptavidin microbeads. The cells were magnetically separated using an LS column and the passingthrough cells were collected.…”
Section: Cell Preparationmentioning
confidence: 99%
“…1 It is reported that sIgA binds viral antigens penetrating across the epithelial layers and effectively protects the host against pathogenic microorganisms in naive mice. [2][3][4] On the other hand, after IgA À/À mice and J-chain À/À mice, both of which are deficient in sIgA, have been immunized by pathogenic microorganisms, they exhibit resistance to mucosal infection by the same pathogens. [5][6][7][8] These findings indicate that sIgA plays a critical role for neutralizing and inactivating microorganisms in the mucous layer of the naive host and is not necessarily required for the guard against pathogenic infection in the host where specific immunity has already been established.…”
Section: Introductionmentioning
confidence: 99%